The Key Ingredient Acacetin in Weishu Decoction Alleviates Gastrointestinal Motility Disorder Based on Network Pharmacology Analysis - Xuan Guo; Yin Xu; Hua-liang Tan; Xiao-juan Wang; Lin Xiao (Mediators of Inflammation)
Background. Gastrointestinal motility disorder is a common gastrointestinal disease, which seriously affects life quality. Traditional Chinese medicine (TCM) has been widely used as an alternative therapy for gastrointestinal motility disorder. Acacetin is a natural flavonoid compound that has antioxidant and anti-inflammatory, antidepressant, and anticancer properties. However, the efficacy of Acacetin in the treatment of gastrointestinal motility disorders has not been studied. Our aim was to investigate the mechanism of Acacetin-alleviated gastrointestinal motility disorder and its efficacy based on network pharmacology. Methods. We performed network pharmacology to predict the active components, match Weishu decoction (WSD) targets in gastrointestinal motility disorders, and investigate its potential pharmacological mechanisms. We performed the GO and KEGG enrichment analysis. In vivo, we investigated the effects of Acacetin in the gastrointestinal motility disorder model. Results. Based on network pharmacological method, the key active ingredient of WSD was identified as Acacetin, and the enrichment signaling pathway was the PI3K-AKT signaling pathway. Acacetin and Mosapride accelerated gastric emptying time, reduced gastric remnant rate, and increased small intestinal propulsion rate. The levels of GAS and MTL were increased after using Acacetin. These results indicated that Acacetin could improve gastrointestinal motility disorders. Among them, high-dose Acacetin showed a better effect. Acacetin could regulate protein and lipid metabolism in mice with gastrointestinal motility disorder. Furthermore, Acacetin could modulate gastrointestinal inflammation and apoptosis. The detection of the PI3K-AKT signaling pathway-related proteins showed that Acacetin improved gastrointestinal motility disorder by inhibiting the activation of the PI3K-AKT signaling pathway. Conclusion. The key ingredient Acacetin in WSD could alleviate gastrointestinal motility disorder by inhibiting the activation of the PI3K-AKT signaling pathway based on network pharmacology analysis. The efficacy and safety of Acacetin treatment provide strong experimental support for the clinical treatment of gastrointestinal motility disorder.